Die Auswanderungsbewegung aus Württemberg nach Amerika, Russland und Palästina aufgrund endzeitlicher Erwartungen - Ehmer, Hermann (Unitas Fratrum, 2018)
After 1800 there emigrated from Württemberg several groups of radical Pietists who were followers of Johann Albrecht Bengel (1687-1752), who had calculated that the second coming of Christ, commencing his thousand-year reign, would occur in 1836. They were seeking a place of safety in the face of the travails of the Last Days. There was disagreement as to where this place was to be found. In any event it would not be in Europe, which was marked by wars and political upheavals. The first to emigrate were about 800 followers of Johann Georg Rapp (1757-1847), who left for the USA in 1804 and successively founded three settlements there on the basis of communal property and celibacy. In 1817 they were followed by the separatists of Rottenacker (on the upper Danube); however, they introduced communal property and celibacy only temporarily in their settlement of Zoar. The victory over Napoleon in 1815 brought into the radical Pietists' view Tsar Alexander I, who seemed to offer a place of safety in the Southern Caucasus. This belief was acted upon by several groups of potential emigrants in various villages in Württemberg, numbering altogether several thousand people, who finally reached their goal -- albeit with considerable losses -- in what is now Georgia. In order to keep people in Württemberg, Korntal was founded in 1819 as a congregation independent of the Church of Württemberg. Christoph Hoffmann (1815-1885), the son of its founder, emigrated to Palestine in 1868 in order to build the Temple of the Last Days. Common to all these groups that emigrated is the fact that, when the expected millennium did not occur, a theological transition to ethical imperatives took place. The settlements founded at that time no longer exist as such, though some of them have become museums.